EMPOWERMENT OF STUDENTS OF NURUR RAUF ISLAMIC BOARDING SCHOOL CAHAYA BARU TLAGAH PEGANTENAN PAMEKASAN THROUGH SEWING AND FASHION DESIGN SKILLS TRAINING - Abd Qadir, Ach. Mahfudz (TOPLAMA, 2025)
This community service program aims to empower students of SMK Nurur Rauf Islamic Boarding School Cahaya Baru Tlagah Pegantenan Pamekasan through sewing and fashion design skills training, with a focus on increasing technical competence, developing creativity based on local culture, and fostering an entrepreneurial spirit. The training is designed to answer students' needs for practical skills that can support economic independence and job opportunities after graduation. The method used is participatory training with a learning by doing approach, where students are actively involved in the entire learning process, from pattern making, fabric cutting, sewing techniques, to developing fashion designs that combine modern elements and typical Madurese motifs. The program was implemented for eight weeks, involving 30 students with diverse ability backgrounds. Evaluation was conducted through observation, product assessment, and questionnaires. The results showed a significant improvement in all aspects of the skills trained. The ability to make patterns increased from 20% to 85%, neat sewing skills from 25% to 90%, and the ability to design local culture-based clothing from 15% to 80%. In addition, students' confidence in marketing their products increased, with 70% of students able to utilize social media as a means of promotion. The resulting social impact includes the formation of a student fashion club and student involvement in exhibitions and product sales. The findings prove that participation-based training, hands-on practice, and integration of local cultural values are effective for empowering pesantren-based vocational school students.